Oral administration of titanium dioxide nanoparticle through ovarian tissue alterations impairs mice embryonic development - Mojtaba Karimipour; Masoumeh Zirak Javanmard; Abbas Ahmadi; Abbas Jafari (Shahid Sadoughi University of Medical Sciences, 2018)
Abstract Background: Titanium dioxide nanoparticle (TiO2NP) is commonly used in industrial products including food colorant, cosmetics, and drugs. Previous studies have shown that oral administration of TiO2NP can be toxic to the reproductive system, but little is known if TiO2NP could be able to affect the functions of the female reproductive system, in particular fertility. Objective: The objective was to evaluate the effects of oral administration of TiO2NP on histological changes in ovaries, pregnancy rate and in vitro fertility in mice. Materials and Methods: In this experimental study, 54 adult female NMRI mice were randomly assigned to two groups: control group (received vehicle orally) and TiO2NP group (received 100 mg/kg/daily TiO2NP solution orally). After 5 wk, pregnancy and in vitro fertilization rates, histological changes in ovaries, malondyaldehyde and estrogen hormone levels in the blood serum were investigated and compared between groups. Results: Our results revealed that TiO2NP administration induced histological alterations in ovary including, degenerating and reduction of ovarian follicles, ovarian cyst formation and disturbance of follicular development. Compared to control, animals in TiO2NP group have shown significant reduction of pregnancy rates and number of giving birth (p=0.04). TiO2NP caused significant reduction in oocyte number, fertilization rate, and pre-implantation embryo development (p<0.001). Furthermore, malondyaldehyde and estrogen hormone levels were significantly (p<0.01) increased in mice received TiO2NP. Conclusion: Our findings suggest that TiO2NP exposure induces alterations on mice ovary resulting in a decrease in the rate of embryo development and fertility.